Analysis Understanding Participant Educate to Theory Rate Reaction - Hayuni Retno Widarti; Sri Yamtinah; Mawardi Mawardi; Deni Ainur Rokhim; Ari Syahidul Siddiq; Afis Baghiz Syafruddin; Titin Sriwahyuni; Zalfa Adhya Rachmanita; Elvira Risva Firda Amalia; Allykha Baharsyah; Tria Anggraini (Postgraduate, University of Mataram, 2022)
Initial understanding is the ability to build early based on experience and knowledge possessed by using grammar that is still relevant to new knowledge. This study aims to explore the experience and knowledge of students to determine the initial understanding of the reaction rates topic. The method used is a questionnaire as a research instrument. In total, 100 students from SMA in Malang, East Java were selected using the purposive sampling method. From these questions, the types of questions are grouped based on alternative answers and sub-material questions and include 3 levels of representation, namely macroscopic, sub-microscopic, and symbolic. Then students' answers are presented and then the students' initial abilities are described following the answers given by students. In teaching and learning activities, students often encounter concepts of knowledge that are constructed independently by students so that when new knowledge is given, there are often differences in understanding or differences in concepts with actual information. The quantitative findings show that in general students' understanding of concepts is 'good', especially on the basic concepts of the reaction rate topic. However, in several sub-materials such as reaction orders, reaction order graphs, and chemical reaction equations in the reaction rate concept topic, there are still conceptual errors experienced by students so improvements and emphasis on concepts are needed in some of these sub-materials so the percentage of correct answers from students is greater from the previous.